2006
DOI: 10.1163/156854006777584278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol-17β on embryos and larvae of the giant freshwater prawn, Macrobrachium rosenbergii (Decapoda, Palaemonidae)

Abstract: The effects of estradiol-17β(E2) on embryos and larvae of the giant freshwater prawn, Macrobrachium rosenbergii (De Man, 1879), were investigated. Embryos, obtained from brooding females within one day of spawning, were exposed to 1, 10, or 50 µg/ml estradiol-17β for 2 days. No significant differences in growth or in survival rate with those of controls were found. However, those exposed to 10 µg/ml E2 showed an increase in hatching rate, in the number of primordial germ cells (PGCs), and in the rate of incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Whereas, our previous study on the growth of estradiol-17β treated embryos showed that it promoted the survival rate [17].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Whereas, our previous study on the growth of estradiol-17β treated embryos showed that it promoted the survival rate [17].…”
Section: Discussionmentioning
confidence: 74%
“…The lethal dose (LD 50 ) was more than 150 µg/ml estradiol-17β. Therefore, estradiol-17β did not affect the survival rates (Pakdeenarong and Damrongphol, 2006). The tolerance dose was more than 150 µg/ ml estradiol-17β.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation